1-Iodotriptycene - Betz, Richard (International Union of Crystallography, 2011)
The title compound, C(20)H(13)I, is a halogenated derivative of triptycene. The molecule shows crystallographic as well as non-crystallographic C (3) symmetry. The asymmetric unit comprises one third of the molecule. Dispersive I⋯I contacts [I⋯I = 3.6389 (3) Å] connect the molecules into dimers. The shortest centroid–centroid distance between two π-systems is 3.8403 (12) Å.